Pengaruh Budaya Organisasi Dan Motivasi Terhadap Kinerja Karyawan Pada Hotel Mercure Makassar - Muhtazib Muhtazib; Mattarima Mattarima; Moh. Af’al (BADAN PENERBIT STIEPARI PRESS, 2021)
this study aims to determine the influence of organizational culture and motivation on employee performance at mercure Makassar Hotel. The method used in this study is the method quantitative. Approach the population in this study were all employees of the mercure Makassar Hotel. The sampling technique used was the slovin technique where the population was a sample of 45 people. The data collected was processed using SPSS. Based on the conclusion that the variable of work organizational culture (X1) has a significant effect on employee performance (Y) partialyy, it is proven that the value of sia is 0,12<0,05 work motivation vanabel (X2) has a significant effect on employee performance (Y) 0,22<0,05